Pembacaan Tafsir Maqashidi terhadap Keselamatan Agama Selain Islam dalam Al-Qur’an - Ihda Hani'atun Nisa' (ILMU USHULUDDIN, 2020)
Religious salvation based on Qur'anic verses seems to contradict each other. The verse about the superiority of Islam breaks the verse that guarantees the safety of religion other than Islam. This is what makes Islam claim to be the only religion that will be saved by God. When people who have religion other than Islam do good during their lives, will they be inferior to those who often do evil? For this reason, in conducting this research, the writer uses the methodology of Maqashidi interpretation of Abdul Mustaqim with the intention that this paper is directed at the benefit of human benefit. The methodology of interpretation that has been done, several conclusions are produced including: First, verses that seem superior are better understood in a generic sense, not as a religion that has been institutionalized as understood today. Secondly, the Koran recognizes the existence of other religions as true religion, so other religions are very likely to achieve salvation. Therefore, a person can be considered safe not because of religious institutions, but with complete surrender in faith and good deeds.